If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2cos(2x) + -1sinx = 0 Remove parenthesis around (2x) 2cos * 2x + -1sinx = 0 Reorder the terms for easier multiplication: 2 * 2cos * x + -1sinx = 0 Multiply 2 * 2 4cos * x + -1sinx = 0 Multiply cos * x 4cosx + -1sinx = 0 Solving 4cosx + -1insx = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add 'insx' to each side of the equation. 4cosx + -1insx + insx = 0 + insx Combine like terms: -1insx + insx = 0 4cosx + 0 = 0 + insx 4cosx = 0 + insx Remove the zero: 4cosx = insx Divide each side by '4osx'. c = 0.25ino-1 Simplifying c = 0.25ino-1
| 2x^2-3x-4(4x+5)= | | 2c=10-3c | | 0=n^2+4n-80 | | 4(n-2)+11=2 | | X3-1/125 | | .6j+3=2j+0.2 | | 0=n^2+4n-89 | | 15y-18=20y+8 | | -3s=7-4s | | 31=y+4 | | a+18=79 | | X-3x+x=-16 | | -3=m+9 | | 3x-7+-3x+7=0 | | 14-3(a+5)=-20 | | 3x-5y=-59 | | 3x-7+-3x-7=0 | | 10.3032y-8.0348=19 | | 4y+12-3=y+3y+9 | | 11x-7+16x-2=180 | | 4x+204=10 | | 10.3032-8.0348=19 | | 21+5c=63 | | 9/10x-3/5=6 | | 2=0.5(3-x) | | 17x+1+16x+8=180 | | 3x+4=52-5x | | 5.81x+4=33.7561+2x | | 4f*6= | | 0=-2sin(x)-sin(2x) | | X+-2y=7 | | 3(5x+2)-3=10x+3 |